Emulation and Malicious Attacks to Doppler and FMCW Radars for Human Sensing Applications - Nallabolu, Prateek; Rodriguez, Daniel; Li, Changzhi (IEEE transactions on microwave theory and techniques, 2023)
This article presents emulation and adverse attack scenarios for Doppler radar-based motion sensors and frequency-modulated continuous-wave (FMCW) radars employed for noninvasive vital signs measurement and human presence sensing. In contrast to existing radar threat models, the proposed model is tuned to mimic two characteristics of a human target measured by radars, i.e., the motion artifacts generated by a walking human and the inherent chest motion. Electronically synthesizing the abovementioned characteristics can interfere with the normal operation of radar systems used for automation, bioauthentication, and surveillance applications. The attacking/emulation systems were realized using commercially available radio frequency (RF) components. The 5.8-GHz benchtop prototypes of the Doppler-and FMCW-mode systems were designed, and experiments were conducted to validate the threat of these systems. First, a single-sideband (SSB) mixer is utilized to electronically modulate the continuous-wave (CW) signal transmitted by a Doppler radar to resemble a walking human subject. Next, fake human targets are injected into an FMCW radar by using an analog phase shifter that mimics the vital sign motion of a real human subject. In addition to impersonating the human vital sign motion, the FMCW mode spoofing system has the capability to alter the range of the human target without requiring any synchronization with the victim radar. The FMCW mode spoofing system successfully deceived two state-of-the-art human detection algorithms. Finally, a brief discussion is presented on the feasibility of using the proposed Doppler and FMCW mode spoofing device architecture as respective radar target emulators.